Profile of women attended by the human milk bank of Odete Valadares Maternity Hospital in Belo Horizonte, Minas Gerais State, Brazil - Rose Hellen Cota Bomfim; Érika Marina Rabelo; Carla da Cruz Santos; Mateus Oliveira Marcelino (Universidade Estadual de Maringá, 2020)
In Brazil, the first "Human Milk Bank" (HMB) was implemented in 1943. Minas Gerais' oldest HMB still in operation was opened on October 19th, 1986 - the HMB of Odete Valadares Maternity Hospital [Maternidade Odete Valadares] (MOV) - and remains as a protagonist service in breastfeeding (BF) promotion in Minas Gerais. MOV has the oldest HMB of Minas Gerais, which is a reference service for maternal and child healthcare in the state. Learning about the profile of the population served by it is important as it allows ensuring and improving the conditions and resources necessary for the service, as well as facilitating the creation of strategies to improve BF support. Thus, the objective of this study was to learn about the profile of women who used MOV's HMB in a month of 2017.  Descriptive study with quantitative approach. As data sources, service forms from November 2017 were used, totaling a final sample of 238 records. The services covered women who gave birth in public and private hospitals. Most mothers were aged between 20 and 34 years old, had borne their first children, were in stable relationships, and had at least 12 years of education. They had access to adequate prenatal care, delivery and postpartum care, as recommended by the Brazilian Health Ministry [Ministério da Saúde] (MS). The main reported complaint: pain. A large number of women sought the service for guidance on breastfeeding as well. The profile of the attended women is similar to that of nursing mothers from other studies. Lack of orientation was one of the main motivations for them to resort to the service, a factor that can be changed by the strengthening of public policies for an adequate follow-up throughout prenatal care.